Unprecedented hailstorms over north peninsular India during February–March 2014. Issue 7 (9th April 2015) - Kulkarni, J. R.; Morwal, S. B.; Narkhedkar, S. G.; Maheskumar, R. S.; Padmakumari, B.; Sunitha Devi, S.; Rajeevan, M.
Abstract Unprecedented, widespread, and devastating hailstorms occurred during February and March 2014 over north peninsular India (study area). A diagnostic study has been carried out to understand the causes for the same. Over the study area the atmosphere was convectively unstable due to the incursion of warm and moist air from Bay of Bengal and Arabian Sea which was overlaid by cold and dry midlatitude westerlies caused due to the unusual upper oceanic heat content of the Pacific Ocean. At the surface and lower levels, anticyclonic flow over the central India produced easterly winds and cyclonic circulation over Arabian Sea at 850 hPa level produced westerly winds over the peninsular India. Meeting of these winds caused convergence of moist air in the lower levels. The troughs in the upper level westerlies provided the divergence in the upper levels. As a consequence of this convergence/divergence structure, synoptic‐scale slow rising motion occurred over the study region. This released the convective instability to cause deep and wide convection with cloud bases at ~1500 m above mean sea level and tops well above the freezing level. Release of latent heat of deposition of water vapor provided extra buoyancy and produced strong updrafts causing explosive growth of the clouds reaching to very high levels and formation of large hails in the clouds. This atmospheric setup was a result of combined effect of planetary and synoptic forcings which persisted for ~3 weeks.